2022
DOI: 10.1371/journal.pone.0261317
|View full text |Cite
|
Sign up to set email alerts
|

The effect of personal relative deprivation on food choice: An experimental approach

Abstract: Growing evidence suggests that relative disadvantage is more relevant than absolute socioeconomic factors in explaining disparities in healthfulness of diet. In a series of pre-registered experiments, we tested whether personal relative deprivation (PRD), i.e. the sense that one is unfairly deprived of a deserved outcome relative to others, results in choosing more palatable, rewarding foods. Study 1 (N = 102) demonstrated the feasibility and effectiveness of a game for inducing real-time experiences of PRD. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(108 reference statements)
0
3
0
Order By: Relevance
“…A notable potential implication of the null effects of perceived societal inequality is that subjective feelings of personal disadvantage may be an important component for perceived inequality in one’s society to contribute to increased appetite and energy intake. Prior cross-societal research has suggested that societies and communities marked by greater economic inequality are associated with higher incidences of obesity and poorer diets [ 24 , 26 , 27 , 52 ], while a growing body of research using experimental methods has revealed that personal feelings of socioeconomic deprivation and unequal outcomes may have a causal contribution to motivations for increased energy intake [ 6 , 7 , 13 , 16 , 18 , 20 ]. The design of the current studies falls between these two bodies of prior research, by experimentally situating individuals and their eating behaviors within a local environment perceived as more (or less) socioeconomically unequal to examine whether perceiving greater class disparities in society could contribute to similar obesogenic behaviors and dietary outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A notable potential implication of the null effects of perceived societal inequality is that subjective feelings of personal disadvantage may be an important component for perceived inequality in one’s society to contribute to increased appetite and energy intake. Prior cross-societal research has suggested that societies and communities marked by greater economic inequality are associated with higher incidences of obesity and poorer diets [ 24 , 26 , 27 , 52 ], while a growing body of research using experimental methods has revealed that personal feelings of socioeconomic deprivation and unequal outcomes may have a causal contribution to motivations for increased energy intake [ 6 , 7 , 13 , 16 , 18 , 20 ]. The design of the current studies falls between these two bodies of prior research, by experimentally situating individuals and their eating behaviors within a local environment perceived as more (or less) socioeconomically unequal to examine whether perceiving greater class disparities in society could contribute to similar obesogenic behaviors and dietary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, when participants were experimentally induced to experience disadvantage in socioeconomic standing compared to others, they consumed more calories from subsequent snacks and meals [ 6 , 13 , 16 ], showed greater sensitivity to energy-signaling sensory properties of beverages [ 17 , 18 ], and exhibited increased circulation of the appetite-stimulating hormone ghrelin [ 19 ], even while controlling for their objective SES (e.g., income). Likewise, various experimental manipulations to generate acute feelings of personal relative deprivation (e.g., receiving unfair material outcomes compared to others) have subsequently led to the selection of larger food portion sizes and preferences for more palatable rewarding foods [ 7 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation